2015
DOI: 10.1210/jc.2014-1984
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Identifies Homozygous GPR161 Mutation in a Family with Pituitary Stalk Interruption Syndrome

Abstract: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 32 publications
0
53
0
1
Order By: Relevance
“…Karaca et al () reported a homozygous missense variant, p. Leu19Gln, in the GPR161 gene as the potential novel cause of pituitary stalk interruption syndrome. In addition, this variant is recognized as likely pathogenic in the ClinVar database.…”
Section: Resultsmentioning
confidence: 99%
“…Karaca et al () reported a homozygous missense variant, p. Leu19Gln, in the GPR161 gene as the potential novel cause of pituitary stalk interruption syndrome. In addition, this variant is recognized as likely pathogenic in the ClinVar database.…”
Section: Resultsmentioning
confidence: 99%
“…Among these mutated genes, transcriptional factor HESX1 ‐mediated repression of Wnt/β‐catenin targets is required for the normal development of anterior forebrain 24; Wnt/β‐catenin signalling promotes midbrain dopaminergic progenitor specification, proliferation and neurogenesis by up‐regulating OTX2 in progenitors 25; Notch signalling has been linked to PROP1 expression 26; GPR161 and CDON , the latest mutations found in patients with PSIS by WES recently, are regulators of Shh pathway 27, 28. Collectively, these pathways seem to be critical to pituitary development.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct facial features of PSIS were reported by Karaca et al . in two affected siblings from one consanguineous family with PSIS: hypotelorism, sparse hair, broad nasal root and thick ala nasi. Another study indicated facial dysmorphic features, including a broad forehead with frontal bossing, anteverted helix, a high nasal bridge with a bulbous nasal tip and a short chin, and deep philtrum with a thin upper lip and sparse fine hair .…”
Section: Clinical Findingsmentioning
confidence: 97%
“…The high frequency of perinatal events is suggestive of an aetiological relationship between perinatal damage and PSIS. However, the existence of familial cases and the presence of accompanying genetic abnormalities, especially midline defects, point to genetic alterations as the underlying pathogenetic mechanism, at least in some patients .…”
Section: Introductionmentioning
confidence: 99%